2020
DOI: 10.1111/1365-2435.13609
|View full text |Cite
|
Sign up to set email alerts
|

Divergent adaptations in resource‐use traits explain how pikas thrive on the roof of the world

Abstract: Life in extreme environments is possible through multilevel adaptations to physical and biotic stresses. At high elevations, species face numerous challenges, besides low oxygen levels, but previous studies have focused on genetic and physiological adaptations to chronic hypoxia while overlooking other key strategies for thriving in alpine landscapes. Here, we investigate resource‐use trait adaptations to extreme elevations using pikas as a model, lagomorphs distributed up to 6,200 m and reaching maximum diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Considerable homoplasy in the morphology of leporid species was identified by Corbet (1983) after examining 21 morphological characteristics for 22 leporid species. More recent morphometric studies of lagomorphs have also found a high degree of homoplasy, low phylogenetic signal, and adaptive divergence in skull shape (Ge et al, 2015;Kraatz and Sherratt, 2016;Feijó et al, 2020). These studies highlight the difficulties in reconstructing a robust phylogeny for lagomorphs, particularly at the intergeneric level, by using morphological data.…”
Section: Phylogenetic Relationships Within Lagomorphamentioning
confidence: 82%
“…Considerable homoplasy in the morphology of leporid species was identified by Corbet (1983) after examining 21 morphological characteristics for 22 leporid species. More recent morphometric studies of lagomorphs have also found a high degree of homoplasy, low phylogenetic signal, and adaptive divergence in skull shape (Ge et al, 2015;Kraatz and Sherratt, 2016;Feijó et al, 2020). These studies highlight the difficulties in reconstructing a robust phylogeny for lagomorphs, particularly at the intergeneric level, by using morphological data.…”
Section: Phylogenetic Relationships Within Lagomorphamentioning
confidence: 82%
“…The O. rufescens lineages in Western and Central Asia formed geographically structured groups, but this pattern of molecular divergence was not paralleled by corresponding morphometric divergence and not entirely compatible with previously recognized taxonomic boundaries. Morphometric analyses, including the type specimens of O. r. rufescens , O. r. regina , O. r. vizier , O. r. shukurovi and O. r. vulturna , demonstrated no variation in morphometric characters among Afghan pikas (Mohammadi et al, 2018), which can be a result of adaptive pressure related to behaviour, lack of divergent selection, high degree of homoplasy, and adaptive divergence in skull shape (Bickford et al, 2007; Dahal et al, 2017; Egea et al, 2016; Feijó et al, 2020; Kraatz & Sherratt, 2016) or strong stabilizing evolution (Mohammadi et al, 2018; Yu et al, 2000). The lack of morphometric diversity in Afghan pikas in external and cranial measurements make taxonomic decisions based on these alone difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Plateau pika, therefore, are considered to play a key role in food chains (Z. Guo et al, 2012; Lai & Smith, 2003; Smith & Foggin, 1999; Y. Zhang et al, 2016), although regarded as a harmful species (Chen et al, 2017; N. Fan et al, 1999; Pang & Guo, 2017; W. Wei et al, 2020), and have an adaptive strategy with a higher mortality and higher regeneration in its population (Nie et al, 2022). On the other hand, alpine creatures have to struggle with environmental and biological stresses through multilevel adaptations in the extreme environmental conditions of lower air temperature and lower atmospheric oxygen concentration (Dahal et al, 2020; Feijó et al, 2020). All of these would result in rodents having higher retained carbon spent on reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al, 2020), and have an adaptive strategy with a higher mortality and higher regeneration in its population (Nie et al, 2022). On the other hand, alpine creatures have to struggle with environmental and biological stresses through multilevel adaptations in the extreme environmental conditions of lower air temperature and lower atmospheric oxygen concentration (Dahal et al, 2020;Feijó et al, 2020). All of these would result in rodents having higher retained carbon spent on reproduction.…”
Section: Role Of Herbivores In Grassland Multifunctionmentioning
confidence: 99%